PENGEMBANGAN PERANGKAT PEMBELAJARAN BERORIENTASI MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Mustafa Mustafa (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
This study aims to: 1) produce problem-based learning model-oriented learning tools that meet valid, practical, and effective criteria, and 2) improve students' problem-solving abilities by using problem-based learning model-oriented learning tools developed. This development research used the Dick and Carey development model which was completed in ten stages. The learning tools produced from this research are: lesson plan (RPP), student activity sheet (LAS), student book (BS), and problem solving ability test (TKM). The subjects in this study were students of class X at SMA Islam Plus Adzkia. The instruments used in the study were the validation sheet, the implementation observation sheet and the test. The results showed that: 1) the learning tools developed met valid, practical, and effective criteria in terms of their respective criteria, 2) there was an increase in students' problem solving abilities using problem-based learning model-oriented learning tools developed to the moderate category.